GIANT MESENTERIC LIPOMA- A RARE TUMOUR OF PAEDIATRIC AGE - Azhar, Muhammad; Zamir, Naima; Jabbar, Abdul (Journal of Ayub Medical College Abbottabad, 2021)
Background: Intraperitoneal Lipomas presenting as huge abdominal mass are uncommon in paediatric age group. We report case of an 11 months old male child, who presented with abdominal distension and constipation. Initial investigations including CT scan and Trucut biopsy of lesion failed to delineate nature of tumour. However, upon surgical excision it turned out to be a rare tumour of mesenteric origin.